Linear Integer Programming and its Innovative Applications in Design of Experiments and Sample Surveys - Baidya Nath Mandal; V.K. Gupta (Journal of the Indian Society of Agricultural Statistics, 2025)
Linear integer programming is a widely used optimization technique to solve various real life problems. The purpose of this article is to present some innovative applications of linear integer programming in the area of design of experiments and sample surveys. It is demonstrated how construction problems of various block designs and different classes of sampling plans can be solved using linear integer programming formulations.